Stereogenic lock in 1-naphthylethanamine complexes for catalyst and auxiliary design : structural and reactivity analysis for cycloiridated pseudotetrahedral complexes - Chen, Jeremy Houguang (2019)
A series of optically active pseudo-tetrahedral five-membered cyclometalated 1-naphthylethanamine iridium(III) complexes were prepared and characterized to analyze the efficacy of the stereogenic conformational lock in both solid and solution phases. The synthesis of the iridacycles was diastereoselective, and the compounds were found to be conformationally rigid. In comparison to its phenyl derivative, the structural lock prevented oxidation of the amine moiety within the five-membered organometallic ring during its synthesis. With up to three stereogenic centers in one of the naphthalene complexes, the stereochemistry of the metallacycle remained stable to both thermal and chemical changes. In terms of catalytic performance, the complexes displayed excellent activity for the asymmetric hydrogen transfer reaction, albeit with modest enantioselectivities.